(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
In the digital era, mobile marketing has emerged as a critical yet unevenly adopted strategy among SMEs in developing economies, where infrastructural disparities between urban and rural areas continue to hinder equitable entrepreneurial growth. This study aims to examine the influence of mobile marketing intensity and geographical location on entrepreneurial success among small and medium-sized enterprises (SMEs) in Uzbekistan, with particular attention to urban–rural disparities. Despite rapid growth in business formation, many enterprises face challenges in achieving sustainable growth and competitive performance due to limited digital adoption and infrastructural constraints. Drawing on Technology Acceptance Theory (TAM), this research posits that entrepreneurs’ perceptions of the usefulness and ease of use of mobile marketing shape its effectiveness in enhancing business outcomes. Using a quantitative survey approach, data were collected from 100 SMEs (50 urban, 50 rural) via Google Forms. Mobile Marketing Intensity (MMI) and Entrepreneurial Success Index (ESI) were measured using Likert scales, while geographical location was coded as a binary variable. Data analysis employed multiple linear regression to assess the direct effects of MMI and location on ESI. Results indicate that mobile marketing intensity has a positive and significant effect on entrepreneurial success, and that urban enterprises outperform rural enterprises due to superior infrastructure, connectivity, and access to resources. This study contributes to the literature by highlighting the strategic role of mobile marketing as a capability that enhances entrepreneurial outcomes in emerging-market contexts and demonstrates how geographical disparities shape its effectiveness. The findings provide actionable insights for policymakers and entrepreneurs seeking to leverage digital marketing to drive business growth across diverse regions.